THE MEANINGS AND IMPLICATIONS OF EDUCATIONAL WORK FOR YOUNG LEGIONNAIRES - Francischetti, Ieda (2020)
When considering a partnership of more than 20 years between Legion Mirim ofMarília and Marilia Medical School (Famema) about the Legionnaire Fellow Program,it was desirable and of great relevance a study for its documentation and evaluation. Itwas aimed to analyse the meaning, strengths and weaknesses of this kind programthrough questionaire application on adolescents that took part of the activities and weregraduated in 2008, 2009 and 2010. The repercussions of that experience in his personaland professional life through qualitative research were discussed. It was evidencied the importance of this activity not only by pre- professionalization but above all, for the ability to socialize and build humanistic references to these young people.